A numerical model for the prediction of the fluid dynamic and mechanical losses of a Wankel-type expansion device. (1st November 2017) - Francesconi, Marco; Antonelli, Marco
Highlights: A model is proposed to predict the real performances of a Wankel expander. The model is based on a lumped parameter approach developed in Matlab®. Different losses were considered in the modelling. A close matching was found between numerical and experimental results. A maximum value of 0.87 at 1250 rpm was found for the isoentropic efficiency. Abstract: This paper presents a numerical model of the fluid dynamic processes and mechanical losses of a Wankel-type expansion device for microgeneration purposes. The prototype was built at the University of Pisa using the rotating parts of a gasoline-fueled Wankel engine. Considering the geometrical features of the prototype, the model simulates the fluid-dynamic losses across the valves, the thermal exchange with the outer ambient and the mechanical losses of the whole mechanism. The numerical results were then validated by the comparison with the pressure cycle obtained at the dynamic test bench using compressed air.